Effect of Solvent Extraction on Yield and Phytochemical Screening of Kedondong (Spondias dulcis) Leaf Extracts - Zahra, Nisrina; Mukhlishah, Neneng Rachmalia Izzatul; Hidayati, Agriana Rosmalina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Kedondong (Spondias dulcis) is empirically used as a cough medicine, skin pain, burns, and antimicrobials. in addition, the people of Kembang Paseban Village, Mersam Subdistrict, Batanghari District, Jambi Province use kedondong leaves as a barut medicine (birth patch medicine). The pharmacological activity of kedondong leaf extract is as a wound healer, antibacterial, anti-inflammatory, antifungal, antipyretic, and as a larvicide. The yield value greatly affects the amount of bioactive content contained in the extract and can affect the results of phytochemical screening. The purpose of this study was to determine the effect of solvent comparison on yield and phytochemical screening of ethyl acetate extract of kedondong leaves. The method used in this study was sonication with a solvent ratio of 1:5 and 1:10, the temperature and time used were 35oC and 30 minutes. The results obtained in the ratio of 1:5 obtained a higher % yield of 5.53% compared to the solvent ratio of 1:10 of 4.67%. While the metabolite compounds identified from ethyl acetate extract are flavonoids and alkaloids.